2018
DOI: 10.1002/jssc.201800207
|View full text |Cite
|
Sign up to set email alerts
|

Thiol‐ene click derived structurally well‐defined per(3,5‐dimethyl)phenylcarbamoylated cationic cyclodextrin separation material for achiral and chiral chromatography

Abstract: In this work, a novel single sulfoether-bridged cationic per(3,5-dimethyl)phenylcarbamoylated-β-cyclodextrin separation material was prepared by thiol-ene click chemistry and characterized by using FTIR spectroscopy, solid-state C NMR spectroscopy and elemental analysis, which confirmed the correct structure. The separation material exhibited a good achiral separation performance for benzene homologues and phenylamine analogs, especially o-xylene and m-xylene, and m-phenylenediamine and o-phenylenediamine can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In most cases, the host molecules are cyclic molecules having a hydrophobic inner cavity and a hydrophilic rim, such as cyclodextrins (CD), cucurbiturils, or calixarenes. Among them, the family of CD macrocycles is most widely studied, with diverse applications in catalysis, separation, food, and biomedicine …”
Section: Molecular‐level Loading Systemmentioning
confidence: 99%
“…In most cases, the host molecules are cyclic molecules having a hydrophobic inner cavity and a hydrophilic rim, such as cyclodextrins (CD), cucurbiturils, or calixarenes. Among them, the family of CD macrocycles is most widely studied, with diverse applications in catalysis, separation, food, and biomedicine …”
Section: Molecular‐level Loading Systemmentioning
confidence: 99%
“…Among the three positional isomers of nitroaniline, the o ‐nitroaniline was eluted first under IPA/hexane mobile phase conditions (as demonstrated in Figure B), however, m ‐nitroaniline was eluted first under methanol/water mobile phase conditions (as shown in Table ). This indicates the main separation mechanisms can be different on the CMP‐CD‐HPS‐packed column under different modes of mobile phase conditions . The results also suggested that the solutes which are not separable under one mobile phase mode could be separated under the other mobile phase mode on the new type of CMP‐CD‐HPS‐packed column.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, the main enantioseparation mechanism appears to be formation of a host‐guest inclusion complex in which the hydrophobic portion of the solute is included in the β‐CD cavity and the substituted 3‐chloro‐4‐methylphenylcarbamate moieties can provide additional interactions, e.g., dipolar‐dipolar interaction and pi‐pi interaction, etc. with the solute . Furthermore, the stable chiral ether spacer linking to the secondary hydroxyl site of β‐CD in the CMP‐CD‐HPS can provide extra steric interaction for the solute enantiomer to enter the β‐CD cavity via the wider torus rim.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works tested the performance of various novel carbamoyl-functionalized cyclodextrin CSPs for sets of model compounds of various structures, including simple flavonoids, such as hesperetin and naringenin [10]. Particularly, a novel single sulfoether-bridged cationic per(3,5dimethyl)phenylcarbamoylated-β-cyclodextrin separation material was prepared by thiolene click chemistry was developed achieving the enantioseparation of naringenin and hesperetin [11]. A new stilbene diamido-bridged bis(βcyclodextrin)-bonded CSP was synthesized allowing a better enantioseparation of flavanones, including naringin and hesperidin, compared to native β-cyclodextrin [12].…”
Section: Introductionmentioning
confidence: 99%